Audit Committee Effectiveness on Earnings Management - Anita Perdana; Umaimah Umaimah; Muhammad Aufa (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine the effect of the number of audit committee meetings and the size of the audit committee on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2016, 2017, 2018 and 2019. Earnings management is measured by Discretionary Accruals using the Modified Jones Model. The population in this study were 160 manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2019. The research data were obtained from the annual reports of manufacturing companies for the period 2016 to 2019. Based on the purposive sampling method, the sample obtained was 40 companies. The hypothesis in this study was tested using multiple linear regression analysis. The results of the test show that the number of meetings and size of the audit committee has a significant effect on earnings management.